2019
DOI: 10.1016/j.ifset.2019.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the impact of high pressure, pulsed electric field and thermal pasteurization on quality attributes of cloudy apple juice using targeted and untargeted analyses

Abstract: The impact of low-oxygen spiral-filter press technology combined with thermal pasteurization (TP), pulsed electric field (PEF) and high pressure processing (HPP) on cloudy apple juice quality was investigated immediately after the treatments and after 3 weeks of storage at 4 C. Based on equivalent levels of microbial safety and desired shelf-life, low and high processing intensities were selected: TP (72 C/15 s; 85 C/30 s), PEF (12.5 kV/cm, 76.4 kJ/L; 12.3 kV/cm, 132.5 kJ/L), and HPP (400 MPa/3min; 600 MPa/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(70 citation statements)
references
References 76 publications
8
58
1
3
Order By: Relevance
“…A study further compared low and high-intensity PEF treatments (12 kV/cm, 80 and 130 kJ/kg) of apple juice, leading to the partial inactivation of POD and PPO for the low PEF treatment (comparable to the observations in our results) and a higher inactivation for the high-intensity PEF treatment, suggested to be related to the thermal impact occurring due to dissipating energy as a result of Joule heating during the PEF treatment [47,49]. Another study of enzyme activity in strawberry puree reported only 3% residual PPO activity after high-intensity PEF at 35 kV/cm, a frequency of 229 Hz, a pulse width of 3.2 and 4.2 µs, treatment time of 1500 µs and bipolar pulses [50], while the minimal residual activity in broccoli juice reached 36% after highintensity PEF (35 kV/cm, 986 kJ/m³, treatment time 2000 µs, bipolar pulse), while lower Compared to other studies, a decrease in the POD and PPO activity to 70% and 55% of the initial activity, respectively, was observed in kale puree after thermal treatment at 70 • C for 2 min [44], while a thermal treatment at 72 • C for 15 s of apple juice, 90 • C for 15 min of strawberry puree and 90 • C for 60 s of broccoli juice resulted in (almost) complete inactivation of POD and PPO [13,47,48]. A study further compared low and high-intensity PEF treatments (12 kV/cm, 80 and 130 kJ/kg) of apple juice, leading to the partial inactivation of POD and PPO for the low PEF treatment (comparable to the observations in our results) and a higher inactivation for the high-intensity PEF treatment, suggested to be related to the thermal impact occurring due to dissipating energy as a result of Joule heating during the PEF treatment [47,49].…”
Section: Residual Enzyme Activity Of Peroxidase (Pod) and Polyphenolosupporting
confidence: 86%
See 2 more Smart Citations
“…A study further compared low and high-intensity PEF treatments (12 kV/cm, 80 and 130 kJ/kg) of apple juice, leading to the partial inactivation of POD and PPO for the low PEF treatment (comparable to the observations in our results) and a higher inactivation for the high-intensity PEF treatment, suggested to be related to the thermal impact occurring due to dissipating energy as a result of Joule heating during the PEF treatment [47,49]. Another study of enzyme activity in strawberry puree reported only 3% residual PPO activity after high-intensity PEF at 35 kV/cm, a frequency of 229 Hz, a pulse width of 3.2 and 4.2 µs, treatment time of 1500 µs and bipolar pulses [50], while the minimal residual activity in broccoli juice reached 36% after highintensity PEF (35 kV/cm, 986 kJ/m³, treatment time 2000 µs, bipolar pulse), while lower Compared to other studies, a decrease in the POD and PPO activity to 70% and 55% of the initial activity, respectively, was observed in kale puree after thermal treatment at 70 • C for 2 min [44], while a thermal treatment at 72 • C for 15 s of apple juice, 90 • C for 15 min of strawberry puree and 90 • C for 60 s of broccoli juice resulted in (almost) complete inactivation of POD and PPO [13,47,48]. A study further compared low and high-intensity PEF treatments (12 kV/cm, 80 and 130 kJ/kg) of apple juice, leading to the partial inactivation of POD and PPO for the low PEF treatment (comparable to the observations in our results) and a higher inactivation for the high-intensity PEF treatment, suggested to be related to the thermal impact occurring due to dissipating energy as a result of Joule heating during the PEF treatment [47,49].…”
Section: Residual Enzyme Activity Of Peroxidase (Pod) and Polyphenolosupporting
confidence: 86%
“…Other studies on the thermal treatment of kale reported a substantial loss of vitamin C in the range of 84% [44], while a different study in apple juice reported a loss of only 10% after PEF and thermal treatment. Only HPP-treated apple juice (600 MPa, 3 min) showed a more significant decrease [47]. In the current study, the increased ascorbic acid/dehydroascorbic acid concentrations after thermal treatment compared to the untreated were unexpected, as ascorbic acid/dehydroascorbic acid is known to be unstable at exposure to high temperatures.…”
Section: Ascorbic Acid/dehydroascorbic Acidcontrasting
confidence: 43%
See 1 more Smart Citation
“…Innovative technologies to stabilize food and beverages have emerged as potential alternatives to conventional thermal processing applied to inactivate the pathogenic and spoilage microorganisms besides endogenous enzymes associated with the degradation of food products during their storage and shelf life. Many of these have a non-thermal process approaches such as pulsed electric field [ 19 ], high-intensity ultrasound [ 20 ], high-pressure processing [ 21 ], ultraviolet-C light [ 22 ], and supercritical carbon dioxide (SC-CO 2 ) technology [ 23 ]. The chemical stability of prebiotic carbohydrates like FOS and other bioactive compounds like beta-ecdysone after stabilization treatments based on emerging technology is an important research issue due to different physical and chemical mechanisms associated with these.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, HPP has been successfully employed to various fruit and vegetable purées and juices [7,8,9,10,11,12,13,14], fruit juice based beverages [15,16], smoothies [17], milk [18,19] cocoyam, Peruvian carrot and sweet potato [20] purple sweet potato nectar [21], peaches [22,23], and pumpkin [24]. In our previous work, we have shown that HPP had no significant ( p > 0.05) impact on the antioxidant activity of potatoes [25].…”
Section: Introductionmentioning
confidence: 99%